Effect of Tropospheric Correction on Long Term Sentinel-1 SAR Measurement - Insan Mafaazan; Panuntun, Hidayat (Journal of Geospatial Science and Technology, 2024)
Sentinel-1 is a remote sensing satellite launched by the European Space Agency (ESA). It is equipped with a radar system that can take measurements over a wide area with high accuracy (cm-mm) and long-term observations. However, one of the main factors affecting long-term SAR measurements’ accuracy is the presence of tropospheric layers within the atmosphere. To determine how much influence this tropospheric effect has, two processing scenarios are performed, namely with and without tropospheric correction, respectively. LiCSBAS is used to perform processing with the time series analysis method. This project uses interferogram data from the Sentinel-1 SAR image with temporal ranging from 2015 to 2023. The research location is in Yogyakarta. Noise due to the presence of tropospheric layer was modeled and removed using Generic Atmospheric Correction Online Service (GACOS). The results show that tropospheric correction can improve the results by reducing the standard deviation in the interferogram phase up to 40%. Based on the results, without tropospheric correction, the maximum vertical displacement is 32.64 mm. With tropospheric correction, the maximum vertical displacement is 34.58 mm. The result suggests that noise from the tropospheric layer might underestimate the vertical displacement. Hence, applying the correction, especially for long-term InSAR measurement, is important.